Targeting epigenetic mechanisms to overcome venetoclax resistance - Prado, Gabriel; Kaestner, Charlotte L.; Licht, Jonathan D.; Bennett, Richard L. (Biochimica et biophysica acta. Molecular cell research, 2021)
The BH-3 mimetic venetoclax overcomes apoptosis and therapy resistance caused by high expression of BCL2 or loss of BH3-only protein function. Although a promising therapy for hematologic malignancies, increased expression of anti-apoptotic MCL-1 or BCL-XL, as well as other resistance mechanisms prevent a durable response to venetoclax. Recent studies demonstrate that agents targeting epigenetic mechanisms such as DNA methyltransferase inhibitors, histone deacetylase (HDAC) inhibitors, histone methyltransferase EZH2 inhibitors, or bromodomain reader protein inhibitors may disable oncogenic gene expression signatures responsible for venetoclax resistance. Combination therapies including venetoclax and epigenetic therapies are effective in preclinical models and the subject of many current clinical trials. Here we review epigenetic strategies to overcome venetoclax resistance mechanisms in hematologic malignancies. •Mutations affecting epigenetic regulation of gene expression are frequent in cancer and impact apoptosis mechanisms.•Venetoclax is a promising therapy for malignancies, but altered expression of BCL2 family members can cause resistance.•Combinations of venetoclax with epigenetic therapies have been approved and demonstrated effective in clinical trials.